Proteomic Signature of Subclinical Coronary Artery Disease in People With HIV: Analysis of the REPRIEVE Mechanistic Substudy. (10th May 2022) - Kolossváry, Márton; deFilippi, Chris; Lu, Michael T; Zanni, Markella V; Fulda, Evelynne S; Foldyna, Borek; Ribaudo, Heather; Mayrhofer, Thomas; Collier, Ann C; Bloomfield, Gerald S; Fichtenbaum, Carl; Overton, Edgar T; et al.
Abstract: Background: People with HIV (PWH) have subclinical coronary artery disease (CAD) despite low traditional atherosclerotic cardiovascular disease (ASCVD) risk scores. Coronary plaque in PWH presents as a unique phenotype, but little is known about the contributions of specific inflammatory pathways to plaque phenotypes in PWH. Methods: The REPRIEVE Mechanistic Substudy enrolled PWH on ART without known cardiovascular disease. We used a targeted discovery proteomics approach to evaluate 246 unique proteins representing cardiovascular, inflammatory, and immune pathways. Proteomic signatures were determined for presence of coronary artery calcium (CAC > 0) and presence of coronary plaque. Results: Data were available for 662 participants (aged 51 [SD 6] years, ASCVD risk score 4.9% [SD 3.1%]). Among 12 proteins associated with both CAC and presence of coronary plaque, independent of ASCVD risk score, the odds ratios were highest for NRP1: 5.1 (95% confidence interval [CI], 2.3–11.4) for CAC and 2.9 (95% CI, 1.4–6.1) for presence of plaque. Proteins uniquely related to presence of plaque were CST3, LTBR, MEPE, PLC, SERPINA5, and TNFSF13B; in contrast, DCN, IL-6RA, OSMR, ST2, and VCAM1 were only related to CAC. Conclusions: Distinct immune and inflammatory pathways are differentially associated with subclinical CAD phenotypes among PWH. This comprehensive set of targets should be further investigated to reduce atherosclerosis and ASCVD in PWH. Clinical Trials Registration: NCT02344290. Abstract : Subclinical coronary artery disease is common among people with HIV, despite relatively low traditional cardiovascular disease risk. We performed a detailed proteomic analysis, demonstrating unique patterns of novel proteins in inflammatory and immune pathways, relating to different plaque phenotypes common.